Contribution of changing diagnostic criteria towardreduction of caries between 1971 and 1997 in children attending the same school in Florianopolis, Brazil - Marcenes W, Freysleben GR, Peres MA (Blackwell Synergy, 2001)
To assess the relative impact of changing diagnostic criteria on changes in the prevalence and severity of caries between 1971 and 1997.